Association of the clinicopathological characteristics and proteinuria remission of pediatric IgAV with nephrotic-range proteinuria: A retrospective cohort study - Zhijuan Kang; Zhijuan Kang; Mai Xun; Zhihui Li; Zuocheng Yang (Frontiers Media S.A., 2022)
BackgroundIgA vasculitis (IgAV) combined with nephrotic-range proteinuria is uncommon, and nephrotic-range proteinuria is considered a risk factor for poor prognosis in children with IgAV. There are few clinical studies with large samples.MethodsChildren with IgAV and nephrotic-range proteinuria who were hospitalized at the Department of Nephrology, Rheumatology and Immunology, Hunan Children's Hospital, from March 2008 to January 2020 were retrospectively studied; the patients were aged ≤18 years and were followed up for ≥12 months. We analyzed clinical characteristics, pathological changes, treatment responses, and their relationships in patients with IgAV combined with nephrotic-range proteinuria.ResultsTwo hundred seventy-seven children with an average age at onset of IgAV with nephritis (IgAVN) of 8.0 years (interquartile range (IQR), 6.0-10.0) were enrolled; 65.7% were aged 6-10 years. The male-to-female ratio was 1.35:1. All children had both nephrotic-range proteinuria and hematuria, 49 (17.7%) had hypoalbuminemia, and 9 (3.2%) had estimated glomerular filtration rate  < 90 (mL/min/1.73 m2). All included children were followed up for at least 1 year. At 3, 6, and 12 months of follow-up, the remission rates of proteinuria in children with IgAV combined with nephrotic-range proteinuria were 27.8%, 62.1%, and 83.0%, respectively, and the remission rates of hematuria were 1.4%, 8.7%, and 35.7%, respectively. In addition, children with age at onset of IgAV with nephrotic-range proteinuria ≥10 years, who were female, who had proteinuria ≥100 mg/kg/24 h, and who had a pathological grade III or above had lower remission rates of hematuria and proteinuria (P < 0.05). Multivariate factor analysis was performed by logistic regression and showed age at onset of IgAVN ≥ 10 years and crescents to be risk factors for nonremission of proteinuria at 12 months of follow-up (P < 0.05).ConclusionsAge at onset of IgAVN, sex, proteinuria level, pathological grade, and crescents significantly affect proteinuria remission in children with IgAV combined with nephrotic-range proteinuria.